Using Geodetic Methods in Road Construction Planning: To What Extent Will It Be Effective? - Nadzir, Zulfikar Adlan; Mhd Irfansyah (PT Penjaminan Infrastruktur Indonesia (Persero), 2024)
Sustainable development is a well-known concept that is widely applied nowadays. One of the applications of this concept is through an effective planning process, such as road construction planning. Cut and fill volume measurement is an integral part of such a process, which utilizes several geodetic methods. The most commonly used instruments are waterpass and electronic theodolite (total station), but there are significant differences in their concepts. Different observation methods of these two tools can affect their effectiveness. Therefore, in this study, the accuracy and efficiency of waterpass and electronic theodolites were measured and analyzed using the cross-section method to gauge the effectiveness of the ABC road construction project in Sumatra. The results show that although the accuracy of the electronic theodolite is lower than that of waterpass, it might be the preferred method because it saves time and reduces the cost of volume measurement, making it both practical and highly efficient.